Multiple belt-drive roof panel seaming apparatus - RIDER TERRY L (2012)
A self-propelled apparatus for the seaming of roof assemblies for a building structure, wherein the apparatus includes multiple belt components configured parallel to one another around the same set of horizontal rollers for the alignment of panel edges in order for engagement of such horizontal rollers to perform the seaming procedure is provided. Such an apparatus exhibits a greatly reduced propensity for potentially marring, distorting, or otherwise misaligning the panel edges due to uniform pressures exerted on the target panel surfaces during use. In addition, the inventive multiple belt-drive apparatus exhibits a much lower potential for slippage during use than an apparatus utilizing multiple rollers to apply proper force during a seaming operation. Reduced crimping, dimpling, creasing, and the like, provides greater reliance of the finished assembled seamed roof in terms of waterproofing and uplift protection as well as to best ensure the seaming apparatus does not jam or otherwise fail during the seaming process itself. A second belt component may also be added in perpendicular relation to the first for further improvements in pressure exertion and thus overall reliability of the seaming operation, preferably, though not necessarily, with multiple belts in place as well. The method of seaming with such an apparatus is also encompassed within this invention.